2019
DOI: 10.1093/ije/dyz127
|View full text |Cite
|
Sign up to set email alerts
|

Headache, tinnitus and hearing loss in the international Cohort Study of Mobile Phone Use and Health (COSMOS) in Sweden and Finland

Abstract: BackgroundMobile phone use and exposure to radiofrequency electromagnetic fields (RF-EMF) from it have been associated with symptoms in some studies, but the studies have shortcomings and their findings are inconsistent. We conducted a prospective cohort study to assess the association between amount of mobile phone use at baseline and frequency of headache, tinnitus or hearing loss at 4-year follow-up.MethodsThe participants had mobile phone subscriptions with major mobile phone network operators in Sweden (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
(31 reference statements)
0
22
0
1
Order By: Relevance
“…Out of the eight identified studies, five were cross‐sectional [Mortazavi et al, 2011; Hegde et al, 2013; Redmayne et al, 2013; Küçer and Pamukçu, 2014; Stalin et al, 2016], two were cohort [Frei et al, 2012; Auvinen et al, 2019], and one was a case–control study [Hutter et al, 2010]. One study provided data both for cohort and cross‐sectional designs [Frei et al, 2012].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of the eight identified studies, five were cross‐sectional [Mortazavi et al, 2011; Hegde et al, 2013; Redmayne et al, 2013; Küçer and Pamukçu, 2014; Stalin et al, 2016], two were cohort [Frei et al, 2012; Auvinen et al, 2019], and one was a case–control study [Hutter et al, 2010]. One study provided data both for cohort and cross‐sectional designs [Frei et al, 2012].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were population‐based [Mortazavi et al, 2011; Frei et al, 2012; Redmayne et al, 2013; Küçer and Pamukçu, 2014; Stalin et al, 2016; Auvinen et al, 2019], while only two were performed in a hospital/clinical setting [Hutter et al, 2010; Hegde et al, 2013]. Two studies included exclusively pediatric populations [Mortazavi et al, 2011; Redmayne et al, 2013], while five studies had exclusively adult populations [Hutter et al, 2010; Frei et al, 2012; Hegde et al, 2013; Stalin et al, 2016; Auvinen et al, 2019], and one study [Küçer and Pamukçu, 2014] included both pediatric and adult subjects. Overall, these studies included 29,093 subjects, of which 16,163 were female, 12,809 were male, and 1 was transgender (one study on 120 subjects did not report the male‐to‐female ratio [Hegde et al, 2013]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, higher scores of depressive symptoms were significantly associated with more frequent physical symptoms, such as headache (26,27), dizziness (28), and fatigue (29,30). However, several studies reported that no such symptoms were found concerning mobile phone radiation and mobile phone use (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%